Injuries among students combining academic studies and elite sports - Flatholm, Emil; Tengman, Eva; Tervo, Taru (Frontiers in Sports and Active Living, 2025)
ObjectiveThe purposes of the study were to examine injury incidence among students engaged in elite sports during their first year of study, and to explore factors associated with injury in this population.MethodsTwo surveys were carried out one year apart. A total of 243 students responded to the initial baseline survey; 111 also responded to a follow-up survey. The surveys addressed injury events and characteristics, sports participation, experienced stress, relaxation, control during leisure time, and study pace.ResultsPrior to commencing their studies, 51% of the athletes had experienced an injury; 54% experienced an injury during their first year of study. A previous injury increased the odds of a new injury (OR = 3.174, p < 0.01). Athletes sustaining an overuse injury prior to studies had higher risk for sustaining a new overuse injury during the first year of studies (OR = 4.312, p < 0.001), while sustaining an acute injury prior to studies did not significantly increase the risk for sustaining a new acute injury. Sex, type of sport, and study pace were not associated with increased odds of injury.ConclusionA concerning 54% injury incidence was found during the first year of study. A previous injury increased the likelihood of sustaining a new injury. The findings suggest that injury-prevention methods should be focused particularly on students who have been injured in the year before they begin their studies.